PENERAPAN MEDIA PEMBELAJARAN “MICROPASCIEN “ UNTUK MENINGKATKAN PEMAHAMAN KONSEP KEMAGNETAN - TEGUH SOEHARTO (LPMP Provinsi DKI Jakarta, 2022)
Understanding the concept of magnetism is an essential material in physics learning. The purpose of this study is to improve the understanding of the concept of magnetism through the application of Micropascien media (Microsoft Paper Science). The research was conducted at SMP Negeri 3 Babelan, Kabupaten Bekasi, Jawa Barat, Academic Year 2020/2021. This study is a class Action study in two cycles. The results showed that in the Pre-Cycle, only 6.67% of the 30 students were able to correctly explain the concept of magnetism. Students' understanding of the concept of magnetism increased from 65.13 in Cycle I to 84.16 in Cycle II. The number of students who understood the concept of magnetism increased from 10.67% to 96.67%. Improved understanding of the concept of magnetism includes indicators of interpreting, presenting examples, concluding and explaining. The research concludes that the use of Micropascien learning media can improve the understanding of the concept of magnetism. The results of the study recommend to science teachers to improve the understanding of the concept of magnetism using Micropascien media.